Flood Estimation using SCS Method for Sungai Johor Catchment, Kota Tinggi - Mohd Arish, Nur Aini; Hamidon, Nuramidah; Hashim, Nor Haslina; Mohd Sari, Kamarul Aini (Penerbit UTHM, 2020)
Malaysia is located in the South East Asia with seasonal monsoons of Southwest and Northeast Monsoons. In December 2006 and January 2007, the Northeast Monsoon had brings heavy rain through series of continuous extreme storms that caused a devastating floods in the northern region of Peninsular Malaysia particularly to Kota Tinggi, Johor. The storms had occurred in in late December 2006 and early January 2007 with a total precipitation in four days exceeding twice of the monthly rainfall in which some places recorded a higher number [1]. Kota Tinggi was under more than 5 m of water during the floods in December 2006 and January 2007[2].